A Fast-Growing Oleaginous Strain of Coelastrella Capable of Astaxanthin and Canthaxanthin Accumulation in Phototrophy and Heterotrophy - Amélie Corato; Thanh Tung Le; Denis Baurain; Philippe Jacques; Claire Remacle; Fabrice Franck (Life, 2022)
Considering the importance of microalgae as a promising feedstock for the production of both low- and high-value products, such as lipids and pigments, it is desirable to isolate strains which simultaneously accumulate these two types of products and grow in various conditions in order to widen their biotechnological applicability. A novel freshwater strain from the genus Coelastrella was isolated in Belgium. Compared to other Coelastrella species, the isolate presented rapid growth in phototrophy, dividing 3.5 times per day at a light intensity of 400 µmol·m−2·s−1 and 5% CO2. In addition, nitrogen depletion was associated with the accumulation of astaxanthin, canthaxanthin, and fatty acids, which reached ~30% of dry weight, and a majority of SFAs and MUFAs, which are good precursors for biodiesel. This strain also accumulated astaxanthin and canthaxanthin in heterotrophy. Although the content was very low in this latter condition, it is an interesting feature considering the biotechnological potential of the microalgal heterotrophic growth. Thus, due to its rapid growth in the light, its carotenogenesis, and its fatty acids characteristics, the newly identified Coelastrella strain could be considered as a potential candidate for biorefinery purposes of both low- and high-values products.